Georgios Trapezuntios and Niccolo Machiavelli on the mixed constitution and Sparta - Steiris, Georgios (ICON, Journal on Byzantine Philosophy, 2023)
Georgios Trapezuntios (1395-c.1472), otherwise known as George of Trebizond, was an eminent scholar of the 15th century, who contributed vastly to the dissemination of ancient Greek philosophy and rhetoric in Renaissance Italy. According to a letter of consolation he sent in the 1420s to Georgius Vatacius Cretensis on the occasion of the latter’s wife’s death, Trapezuntios was fascinated by the Spartan culture. In the letter, he frequently refers to Pseudo-Plutarch’s Consolatio ad Apollonium, especially to the passages where Pseudo-Plutarch praises the Spartan attitude towards death. A few decades later, in 1451, Trapezuntios translated the Platonic Laws, the careful study of which led him to express the view that the Platonic philosophy was what inspired Venice’s founding fathers to establish their mixed constitution. As proposed by modern scholarship, Trapezuntios specifically refers on passages where Plato praises the Spartan constitution. Further, in his Comparatio Philosophorum Platonis et Aristotelis, Trapezuntios discusses Venice’s mixed constitution and its relation to the Spartan polity. As a result, he was responsible, along with Aristotle and Polybius, for the reappraisal of the Spartan constitution in 15th-century Italy. Later, Niccolo Machiavelli (1469- 1527) argued in support of the mixed constitution and praised Sparta more than any other Greek state, although he believed in Rome’s political superiority. Machiavelli extolled Lycurgus for giving Sparta durable laws. In this paper, I set to examine how Trapezuntios and Machiavelli approached the ancient sources that informed them about the Spartan constitution, and how they contributed to the birth of the political myth of Sparta in the Renaissance. Finally, I suggest that Trapezuntios’ views on the Venetian constitution presuppose Polybius’ and Plutarch's rather than Plato’s texts.